New Trends in Cognitive Ageing and Mild Cognitive Impairment - Facal, David; Spuch, Carlos; Rodriguez, Sonia Valladares (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the process of cognitive ageing, considering the increase in cognitive impairment associated with the aging of the population and the related care impact. Special attention is given to cognitive health changes linked to the increase in life expectancy, including the role of subjective factors; the link between cognitive function, mobility and functionality; and the potential role of digital technologies, including computerized cognitive tests and virtual reality environments.